2019
DOI: 10.3390/jcm8010098
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sex Differences and Diabetes on Coronary Atherosclerosis and Ischemic Heart Disease

Abstract: Cardiovascular diseases (CVD) including coronary artery disease (CAD) and ischemic heart disease (IHD) are the main cause of mortality in industrialized countries. Although it is well known that there is a difference in the risk of these diseases in women and men, current therapy does not consider the sexual dimorphism; i.e., differences in anatomical structures and metabolism of tissues. Here, we discuss how genetic, epigenetic, hormonal, cellular or molecular factors may explain the different CVD risk, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 115 publications
(142 reference statements)
5
40
1
1
Order By: Relevance
“…Given that the underlying mechanism by which diabetes might confer this greater excess risk to women for other incident cardiovascular diseases is still unknown [38], it is challenging to explain why we do not see a sexspecific effect for the relationship between diabetes and PAD, which is also a type of cardiovascular disease. However, one possible explanation lies in the finding that the more pronounced increase in relative risk for CVD events in women with diabetes compared to men appears, in part, to reflect the lower disease risk in women compared with men without diabetes [16].…”
Section: Sex Differences In Other Cvdsmentioning
confidence: 88%
“…Given that the underlying mechanism by which diabetes might confer this greater excess risk to women for other incident cardiovascular diseases is still unknown [38], it is challenging to explain why we do not see a sexspecific effect for the relationship between diabetes and PAD, which is also a type of cardiovascular disease. However, one possible explanation lies in the finding that the more pronounced increase in relative risk for CVD events in women with diabetes compared to men appears, in part, to reflect the lower disease risk in women compared with men without diabetes [16].…”
Section: Sex Differences In Other Cvdsmentioning
confidence: 88%
“…The increase in AGE levels, secondary to hyperglycemia, increases the receptor for AGE (RAGE), resulting in increased ROS production and leading to activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling with the production of inflammatory cytokines [20]. Excessive AGE formation leads to the loss of pericytes, increased platelet aggregation, and endothelial dysfunction, all abnormalities that can promote pro-coagulant status with consequent ischemia damage [21].…”
Section: Figurementioning
confidence: 99%
“…Hypertension, diabetes, sex differences, obesity, smoking and high cholesterol are the most important risk factors for cardiovascular diseases (2,3). Recent studies have demonstrated that the abnormal accumulation of plasma homocysteine (Hcy) is a risk factor for cardiovascular diseases, which may lead to myocardial cell dysfunction by inducing apoptosis (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%